Collocational and idiomatic aspects of composite predicates in the history of English - Brinton, Laurel J.; Akimoto, Minoji, 1941- (Studies in language companion series, 1999)
The focus of this carefully selected volume concerns the existence, frequency, and form of composite/complex predicates (the "take a look" construction) in earlier periods of the English language, an area of scholarship which has been virtually neglected. The various contributions seek to understand the collocational and idiomatic aspects of these structures, as well as of related structures such as complex prepositions (e.g., "on account of") and phrasal verbs (e.g., "look up"), in their earliest manifestations. Moreover, study of these constructions at the individual stages of English leads.